Homeopathy in the Treatment of Viral Diseases: Scientific Data on the Basis of which it is Possible to Reason Scientifically on the Therapeutic Potential of Homeopathic Medicines - De Giorgio, Giovanni; Tarro, Giulio (British Journal of Healthcare and Medical Research, 2025)
Homeopathy, discovered about two centuries ago by Samuel Hahnemann, is a therapy based on the so-called “law of similarity”, or, “similia similibus curentur”, according to which “similar” is cured by “similar”: the patient is treated with the administration of “small doses” of substances that, if administered in “high doses” to a healthy subject, would cause “similar” symptoms to those suffered by the patient. Based on the law of similarity, various pathologies are treated with homeopathy, including viral pathologies. Various scientific studies demonstrate the effectiveness of homeopathy in some viral pathologies, even serious ones, and several scientific articles report extremely interesting data that have been acquired during important and rigorous in vitro studies, in vivo studies and clinical studies. Although studies on homeopathy need to be further explored, with regard to the treatment of viral pathologies, it is necessary to take into account the scientific data currently available on the basis of which it is possible to scientifically reason about the therapeutic potential of homeopathic "small doses" and their efficacy demonstrated through some important in vivo studies, in vitro studies and clinical studies.